Information security methodological proposal, for sending biomedical signals in rural telehealth systems - Auccahuasi, Wilver (2020)
ABSTRACT Information and communication technologies are revolutionizing the different areas of knowledge, and medicine is an area where the uses of new technologies are put into practice for the well-being of people. But these new ways of using technology produce a high risk when information is required to be transmitted, either due to the loss of information also due to the risk that the information may be altered for different reasons and due to the theft of information. It is for these reasons that it is necessary to have certain mechanisms to be able to achieve the maximum integrity of the information, in this work a methodology is presented to be able to safely transmit information from the different medical teams to medical information based on an organization of the information, in order to present in a practical way its possible implementation in the development of systems to develop TELESALUD, the protocol is based on the good practices provided by the HL7 standard for the management of clinical information as well as the interoperability between the systems of information and medical equipment that are operating remotely, as results a proposal is presented to be able to carry out rural TELESALUD, oriented to the measurement of patients using various equipment and their transmission to other hospital centers for their diagnosis.